Standard Bases for Ideals in the ring K[[X]] - Cáceres Huamán, María del Carmen (2023)
This article presents the standard bases for ideals, in the context of formal power series rings over a ﬁeld, employing the Buchberger’s Algorithm under certain restrictions. It also shows several characterizations of equivalent standard bases. This allows us to calculate the codimensions of ideals in rings of formal power series.